Gestión administrativa y su incidencia en la operatividad de la empresa pública de movilidad de la mancomunidad de Cotopaxi, año 2022-2023 - Angueta Madrid, Kerly Katherine (2024)
The research "Administrative management and its impact on the operativity of the public mobility company of the mancomunity of Cotopaxi, year 2022-2023" had the following objectives: to evaluate the administrative processes applied in the EPMC, to establish the degree of satisfaction of the clients/users and to evaluate the operability by means of indicators. The research was field, descriptive and analytical, using analytical, deductive, inductive and logical-historical methods; an interview guide and questionnaire were prepared for a sample of 234 vehicle owners. The results indicate that in planning it does not affect the normal performance, in organization it has a low impact on the administrative management, in management there are processes that are not well directed so there would be problems in the institutional management and in control the processes are not being carried out properly, especially in the implementation of strategies, control and mechanisms to monitor the operational activities in the EPMC. EPMC's operative determines that the number of users increased in some services, while in others it has decreased, the satisfaction of EPMC's clients/users is high among the respondents regarding the quality of services. It is concluded that control at EPMC is not efficient and, although it is an element of the management process that includes all the activities that are carried out to ensure that the activities of the EPMC are carried out in a timely manner, the quality of the services provided by the EPMC is high.